Influence mechanism of disk surface roughness on the flow characteristics of low-speed marine gas turbine rotor–stator cavity - Wang, Chuan; Yao, Yulong; Yu, Hao; Wang, Hui; Chang, Hao (Physics of fluids (1994), 2025)
In marine gas turbines, surface roughness on both rotating and stationary disk surfaces can markedly alter flow structures within the rotor–stator cavity, leading to energy losses that remain poorly quantified in the literature. This study presents the first systematic computational fluid dynamics investigation of centripetal through-flow rotor–stator cavities subject to rotor roughness (RR), stator roughness (RS), and combined rotor–stator roughness (RRS) across six rotational speeds (n = 1000–4000 rpm) and a broad roughness range (equivalent surface roughness ks = 0–76.81 μm). Numerical simulations are rigorously validated against bench-scale measurements, ensuring high fidelity of the predicted flow fields and performance metrics. Our results demonstrate that rotor roughness dominantly amplifies boundary-layer disturbances, expands the core vortex region, and induces local vortical structures, whereas stator roughness exerts a secondary influence. Under RRS conditions, cavity performance trends align closely with the RR case. Quantitatively, rotor torque coefficient increases by up to 35% and axial thrust coefficient by up to 18% at ks = 76.81 μm. Finally, we derive and validate empirical correlations incorporating roughness terms for rapid estimation of torque and thrust variations in engineering practice. This work provides actionable insights and practical tools for predicting and mitigating performance penalties due to disk surface roughness in marine gas turbine rotor–stator cavities.